2004
DOI: 10.1104/pp.104.049502
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Physiological Analysis of the Two Plastidic ATP/ADP Transporters from Arabidopsis

Abstract: Arabidopsis (Arabidopsis thaliana) possesses two isoforms of plastidic ATP/ADP transporters (AtNTT1 and AtNTT2) exhibiting similar biochemical properties. To analyze the function of both isoforms on the molecular level, we examined the expression pattern of both genes by northern-blot analysis and promoter-b-glucuronidase fusions. AtNTT1 represents a sugar-induced gene mainly expressed in stem and roots, whereas AtNTT2 is expressed in several Arabidopsis tissues with highest accumulation in developing roots an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
121
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(126 citation statements)
references
References 38 publications
4
121
1
Order By: Relevance
“…However, because of missing sulfation reactions in thylakoids, a PAPS (or PAP) transport across the thylakoid membrane is certainly not of physiological relevance. On the other hand, the IEM of plastids contains well-characterized ADP/ATP transporters (NTTs), which are primarily involved in ATP supply to chloroplasts during darkness (Neuhaus et al, 1997;Reiser et al, 2004). It has been demonstrated that mutants defective in NTT function do not survive extended darkness followed by illumination (Reinhold et al, 2007).…”
Section: The Physiological Role Of Paps Transport In Plastid Envelopementioning
confidence: 99%
“…However, because of missing sulfation reactions in thylakoids, a PAPS (or PAP) transport across the thylakoid membrane is certainly not of physiological relevance. On the other hand, the IEM of plastids contains well-characterized ADP/ATP transporters (NTTs), which are primarily involved in ATP supply to chloroplasts during darkness (Neuhaus et al, 1997;Reiser et al, 2004). It has been demonstrated that mutants defective in NTT function do not survive extended darkness followed by illumination (Reinhold et al, 2007).…”
Section: The Physiological Role Of Paps Transport In Plastid Envelopementioning
confidence: 99%
“…Within the past decade, the physiological functions of the two ATP transporters (NTTs) in Arabidopsis have been characterized. Extensive analysis of NTT antisense, RNA interference, and knockout plants revealed distinctive physiological roles of the NTTs in different types of plastids (Reiser et al, 2004).…”
Section: Reverse Genetics: a Powerful Toolmentioning
confidence: 99%
“…Plant growth was performed at 228C and 120 mmol quanta m 22 s 21 in a 10-h-light/14-h-dark regimen. For growth experiments with 5-FU, 5-FD, and 5-FO, surface-sterilized seeds were sown on Murashige and Skoog plates as described earlier (Reiser et al, 2004). Growth of seedlings in hydroponic culture was performed as described by Scheible et al (2004).…”
Section: Cultivation Of Plantsmentioning
confidence: 99%